2022
DOI: 10.3389/fpsyg.2022.887940
|View full text |Cite|
|
Sign up to set email alerts
|

How Mindfulness Affects Life Satisfaction: Based on the Mindfulness-to-Meaning Theory

Abstract: Life satisfaction is the general evaluation of the individual’s life, which is of great significance to achieving a better life. The purpose of the present study was to investigate the mediating effect of core self-evaluation, positive affect, and negative affect in the relationship between trait mindfulness and life satisfaction based on the Mindfulness-to-Meaning theory. 991 Chinese undergraduates (692 females, 299 males) completed the Mindful Attention Awareness Scale, the Core Self-Evaluations Scale, the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…That is, individuals in the high mindfulness profile exhibited the highest well-being and mental health, those in the low mindfulness profile reported the lowest levels of both, and those in the moderate mindfulness profile fell in between. These findings align with numerous previous variable-centered findings (Prazak et al, 2012;Alleva et al, 2014;Zimmaro et al, 2016;Mayer et al, 2019;Li et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…That is, individuals in the high mindfulness profile exhibited the highest well-being and mental health, those in the low mindfulness profile reported the lowest levels of both, and those in the moderate mindfulness profile fell in between. These findings align with numerous previous variable-centered findings (Prazak et al, 2012;Alleva et al, 2014;Zimmaro et al, 2016;Mayer et al, 2019;Li et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is possible that over the course the year, perceptions of stress shifted significantly. Likewise, Li et al. (2022) assert negative experiences have a stronger positive impact on well-being, and therefore, mindfulness may have a more prominent role in reducing negative affect via positive reappraisal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that over the course the year, perceptions of stress shifted significantly. Likewise, Li et al (2022) assert negative experiences have a stronger positive impact on well-being, and therefore, mindfulness may have a more prominent role in reducing negative affect via positive reappraisal. Using MMT, they found that both cognition and emotion mediated the relationship between trait mindfulness and life satisfaction (2022).…”
Section: Jmd 421mentioning
confidence: 99%
“…Several previous studies have examined the effects of psychological interventions on athletic performance and motivation. For example, Li et al [7] investigated the impact of a mindfulness-based intervention on the performance of youth soccer players, while Huang et al [8] studied the effects of a goal-setting intervention on the motivation and performance of young swimmers. Wilson et al [9] examined the effects of a self-talk intervention on the motivation and performance of youth basketball players.…”
mentioning
confidence: 99%